Impact of an incentive‐based prenatal smoking cessation program for low‐income women in Colorado. Issue 1 (6th November 2019) - Polinski, Kristen J.; Wolfe, Rachel; Peterson, Anne; Juhl, Ashley; Perraillon, Marcelo Coca; Levinson, Arnold H.; Crume, Tessa L.
Abstract: Objective: To assess birth outcomes and cost‐savings of an incentive‐based prenatal smoking cessation program targeting low‐income women in Colorado. Design: Prospective observational cohort with nonequivalent population control groups. Sample: Program participants ( n  = 2, 231) linked to the birth certificate to ascertain birth outcomes compared to two reference populations from Pregnancy Risk Assessment Monitoring System (PRAMS) and Colorado live births based on the birth certificate. Measurements: Tobacco cessation metrics in the third trimester of pregnancy, neonatal low birth weight (<2, 500 g), preterm birth (birth at <37 weeks gestation), neonatal intensive care unit (NICU) admission and maternal gestational hypertension. Cost‐savings and return on investment (ROI) were projected using average Medicaid reimbursement. Results: Infants of mothers enrolled in the program had a lower risk of low birthweight (RR = 0.86; 95% CI = 0.75, 0.97), preterm birth (PTB) (RR = 0.76; 95% CI = 0.65, 0.88) and neonatal intensive care unit (NICU) admission (RR = 0.76; 95% CI = 0.66, 0.88) compared to the birth certificate population, corresponding to a ROI of $7.73 and an individual cost savings of $6, 040. Compared to PRAMS, infants of enrolled mothers had a lower risk of PTB (RR = 0.72; 95% CI = 0.53, 0.99) and NICU admission (RR = 0.45; 95% CI = 0.32, 0.62), corresponding to an ROI of $2.79 and an individual cost savings of $2, 182. Conclusions: We found a reduction of adverse birth outcomes, and cost savings.